Le potentiel éducatif du design fiction dans le développement de la pensée critique - Géraldine Wuyckens (ReS Futurae)
Design fiction is a design practice that uses science fiction to imagine possible futures for technologies. Originally used in the fields of traditional design and human-computer interaction, design fiction offers a real potential for education in a school environment. More specifically, design fiction encourages young people to put themselves in the shoes of inventors of the future and to contextualise their inventions in a near-future world through the production of speculative scenarios. Beyond the prototyping aspect, this approach encourages them to think about the issues surrounding the objects they create and the relationships they have with everyday technologies. This article presents a pedagogical method using design fiction in a media education context to develop learners’ critical thinking. First, I explain what design fiction is and how it relates to fiction and science fiction. Second, I present the pedagogical method developed in collaboration with my partner to use design fiction in schools. I detail the activities carried out with the pupils during the project to highlight in the following section the contributions of design fiction in fostering critical thinking. The conclusion lists design principles for any researcher or teacher wishing to use design fiction in a learning context.